The «Theory of Mausoleums» or the Regional Features of Spiritual Memorial Architecture of the Golden Horde Era in the Ural-Volga Region (historical and ethnographical aspects of the problem) - G.N. Garustovich (Золотоордынское обозрение)
This article reviewes the features of the funeral ceremonies in the Muslim mausoleums of 14th century in the Ulus of Jochi (Ak-Horde). The author states that there was an independent architectural school in cultic memorial architecture of the Golden Horde. This school can be recognized in its stone and brick mausoleums. The author analyses features of the funeral tradition of the period when the dual faith believes (period of the nascence of Islam) was spread all over the steppe empire. The Muslim burials appeared in the times of Islamization, a policy pursued by Uzbeg khan and his successors in 14th century. The mausoleums were built for the aristocracy. The author believes that they also served as a monumental propaganda of Islam. From the very beginning, those monumental buildings in the steppe areas were turned into the venues with the social significance, into the sacral places for worshiping the ancestors, into the sacral monuments of the tribal territories. At the same time, the mausoleums, initially built as the family burials of the elite of the nomad empire, were keeping their first function. Thus, the empire’s ruling class was trying to win over the aristocratic members of the society and get their loyalty in the process of conversion to the new monotheistic religion, which had become empire’s new ideology. Islam in the Ulus of Jochi was not accepted immediately and had to coexist with different religion in the 14th century. Muslim mausoleums contain significant number of the heathen artifacts (jewelry, clothes etc.), which can serve as the evidence of the coexistence of heathenism and Islam. In general, cultic memorial architecture accomplished its «mission». The Golden Horde was successfully Islamized. Over time, the Turkic people under the empire converted to Islam thus becoming the part of the world Muslim civilization.